2011
DOI: 10.1007/s12263-011-0224-z
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienols and breast cancer: the evidence to date

Abstract: Breast cancer is the second most frequent cancer affecting women worldwide after lung cancer. The toxicity factor associated with synthetic drugs has turned the attention toward natural compounds as the primary focus of interest as anticancer agents. Vitamin E derivatives consisting of the well-established tocopherols and their analogs namely tocotrienols have been extensively studied due to their remarkable biological properties. While tocopherols have failed to offer protection, tocotrienols, in particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…T3s have been shown to inhibit the growth of various cancer cells including breast cancer without affecting the growth of normal cells [58]. T3s have been evaluated in vitro and in vivo as powerful cancer chemotherapeutic/preventive agents, yet their exact mechanisms of action on cell death and other inhibitory pathways are unknown [9,10,7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…T3s have been shown to inhibit the growth of various cancer cells including breast cancer without affecting the growth of normal cells [58]. T3s have been evaluated in vitro and in vivo as powerful cancer chemotherapeutic/preventive agents, yet their exact mechanisms of action on cell death and other inhibitory pathways are unknown [9,10,7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Tocotrienols showed significant in vivo anticancer activity in breast cancer, pancreatic cancer and melanoma. Their anticancer activity is mediated by apoptosis, autophagy, and NFkB mediated pathways [48][49][50][51][52].…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Caner is the most lethal disease in humans with very low survival rate [6,7] because of the cancer associated mutations in cells, and metastasis [8,9]. Vitamins and their sources have their key role as they have shown to have potent anticancer effect against various types of cancer with minimum toxicity [6,[10][11][12][13][14]. Several in vivo and human studies indicated the role of Vitamin E, especially γ-tocotrienol, being the potent anticancer agent against variety of cancers compared to other isoforms [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that some natural killer cells increased when tocotrienols were supplemented in mice. These contested MCF-7 breast cancer cells in humans (2). Research has also shown that oral administration of vitamin E supplements (tocotrienols and tocopherols) affects the human immune system, proliferation of spleen cells and lymphocytes (35).…”
Section: Biological Functions Of Tocotrienolsmentioning
confidence: 99%
“…Evans and Bishop (1922) were the first to discover vitamin E as a factor in the diet of rats that helped boost their reproduction. Vitamin E was isolated for the first time by Gladys Emerson at the University of California, Berkeley in 1935, followed by structural elucidation by Erhard Fernholz in 1938 and its first synthesis by a team of scientists headed by Paul Karrer in 1939 (2). The antioxidant activity of vitamin E prevents lipid peroxidation propagation and is beneficial for human health (3).…”
mentioning
confidence: 99%